Modeling a process of filling the mold during injection molding of polymeric parts - Kulik, Tetiana; Synyuk, Oleh; Zlotenko, Borys (Eastern-European Journal of Enterprise Technologies, 2017)
We investigated the process of filling the molds used in injection molding with the molten polymer, particularly, the formation of lines of seals in the presence of several intake openings in the mold or when the melt flows round the obstacles. As a result of analysis of the designs of molds we established main causes of the low quality of molded products. It is shown that the presence of seals significantly reduces quality of the polymeric goods. Accordingly, it is recommended to design the molds so that it is possible to avoid formation of seals in the products. Alternatively, if this is not possible, it is necessary to ensure that the seals are absent in places that accept maximal loads. In the present work, we developed a mathematical model of the dynamics of motion of a viscous fluid with free surface in the mold cavity. The model includes the Navier-Stokes equations, the equation of continuity and the Laplace equations. By solving the specified system of equations, we determined rate components of a two-dimensional flow and pressure of the melt in the process of filling a mold. Based on the application of the method of markers and cells, we carried out analytical studies into formation of the line of seals in the polymeric products made by injection molding. It is proven that the position of seals in the finished product depends on the geometry of the mold cavity and the location of intake openings and do not practically depend on the temperature parameters of the process. It was established that dependences of rate of the melt flow front on the height and width of the mold are non-linear in nature, which must be considered when estimating duration of technological cycle of injection molding. The use of the results of present research makes it possible to reduce the cost of designing molds for producing polymeric products with improved operational properties. In order to confirm adequacy of the mathematical model to actual processes, we conducted experimental research. A maximal deviation of experimental data from analytical data does not exceed 12 %